D‐dimer testing for early detection of venom‐induced consumption coagulopathy after snakebite in Australia (ASP‐29). Issue 4 (7th June 2022) - Isbister, Geoffrey K; Noutsos, Tina; Jenkins, Shane; Isoardi, Katherine Z; Soderstrom, Jessamine; Buckley, Nicholas A
Abstract: Objective: To assess the accuracy and marginal value of quantitative D‐dimer testing for diagnosing venom‐induced consumption coagulopathy (VICC) in people bitten by Australian snakes. Design, setting: Analysis of data for suspected and confirmed cases of snakebite collected prospectively by the Australian Snakebite Project, 2005–2019, from 200 hospitals across Australia. Participants: 1363 patients for whom D‐dimer was quantitatively assessed within 24 hours of suspected or confirmed snakebite. Main outcome measures: Diagnostic performance of quantitative D‐dimer testing for detecting systemic envenoming with VICC (area under the receiver operating characteristic curve, AUC); optimal D‐dimer cut‐off value (maximum sum of sensitivity and specificity). Results: D‐dimer values exceeded 2.5 mg/L within three hours of the bite for 95% of patients who developed VICC, and were lower than 2.5 mg/L for 95% of non‐envenomed patients up to six hours after snakebite. The AUC for diagnosing envenoming with VICC on the basis of quantitative D‐dimer testing within six hours of snakebite was 0.97 (95% CI, 0.96–0.98; 944 patients). Diagnostic performance increased during the first three hours after snakebite; for quantitative D‐dimer testing at 2–6 hours, the AUC was 0.99 (95% CI, 0.99–1.0); with a cut‐off of 2.5 mg/L, sensitivity was 97.1% (95% CI, 95.0–98.3%) and specificity 99.0% (95% CI, 97.6–99.6%) for VICC. For 36 patients with normal international normalised ratio (INR) and activated partial thromboplastin time (aPTT) values 2–6 hours after snakebite, the AUC was 0.97 (95% CI, 0.93–1.0); with a cut‐off of 1.4 mg/L, sensitivity was 94% (95% CI, 82–99%) and specificity 96% (95% CI, 94–97%). In all but one of 84 patients who developed VICC‐related acute kidney injury, D‐dimer values exceeded 4 mg/L within 24 hours of the bite. Conclusion: D‐dimer concentrations assessed 2–6 hours after snakebite, with a cut‐off value of 2.5 mg/L, could be useful for diagnosing envenoming with VICC.